Four‐Component Relativistic DFT Calculations of 13C Chemical Shifts of Halogenated Natural Substances. Issue 51 (6th November 2015) - Casella, Girolamo; Bagno, Alessandro; Komorovsky, Stanislav; Repisky, Michal; Saielli, Giacomo
Abstract: We have calculated the 13 C NMR chemical shifts of a large ensemble of halogenated organic molecules (81 molecules for a total of 250 experimental 13 C NMR data at four different levels of theory), ranging from small rigid organic compounds, used to benchmark the performance of various levels of theory, to natural substances of marine origin with conformational degrees of freedom. Carbon atoms bonded to heavy halogen atoms, particularly bromine and iodine, are known to be rather challenging when it comes to the prediction of their chemical shifts by quantum methods, due to relativistic effects. In this paper, we have applied the state‐of‐the‐art four‐component relativistic density functional theory for the prediction of such NMR properties and compared the performance with two‐component and nonrelativistic methods. Our results highlight the necessity to include relativistic corrections within a four‐component description for the most accurate prediction of the NMR properties of halogenated organic substances. Abstract : When the going gets heavy, relativistic DFT gets going : The 13 C NMR spectra of natural substances containing bromine and/or iodine, such as those often obtained from marine sources, can be extremely complex. Relativistic DFT calculations, including spin‐orbit effects, have a high predictive power and thus represent an effective tool in the structure elucidation of these substances.